Shisha Consumption and Presence of Cotinine in Saliva Samples among Students in Public Universities in Coastal Kenya - Abdulrehman Halima Allahdad; Moses Ngari; Cromwell Mwiti Kibiti; Rahma Udu Yusuf; Sylvia Mutua; Valentine Budambula (Wiley, 2024)
Background. Despite the well-known adverse health effects of tobacco, shisha use among students in tertiary institutions remains a public health concern. In Kenya, the literature on status of shisha after the 2017 ban is scanty. This study sought to ascertain actual shisha use among university students along the coastal strip. Methods. We investigated confirmed and self-reported shisha use. Using proportionate-to-size and snowball sampling methods, 380 respondents were enrolled from three universities. Sociodemographic characteristics and self-reported history of shisha use were documented using a participant-assisted questionnaire. Actual shisha use was determined qualitatively using 6 panel plus alcohol saliva test kit that detected cotinine use among other selected drugs. Results. Of the 380 participants, 278 (73%) were males and their median (IQR) age was 22 (20-23) years. This study reports 29% current use based on testing positive for cotinine. Among those who reported current ever use of shisha, 19% tested positive for cotinine, respectively. In the multivariable analysis, being separated (adjusted risk ratio (aRR): 2.06 (95% CI: 1.45-2.94)) compared to being single and studying for a degree compared to a diploma (aRR: 1.32 (95% CI: 1.10-1.58)) were associated with cotinine positive. The 4th year of study (aRR: 1.68 (95% CI: 1.22-2.33)) compared to the 1st year and reported knowledge of shisha (aRR: 1.84 (95% CI: 1.18-2.87)) were associated with cotinine positive. Conclusion. Nearly one-third of university students along the Kenyan coast are active shisha users. Saliva testing for cotinine is a more reliable method of reporting tobacco use. We recommend upscaling of health education, re-enforcement of the current ban on shisha consumption by concerned authorities, and saliva testing for cotinine while assessing current tobacco use.